Analisis Spasial Potensi Dan Status Kerusakan Tanah di Kecamatan Sawan Kabupaten Buleleng - SAMUDRA, KEMAL; SUPADMA, A.A. NYOMAN; KUSMIYARTI, TATI BUDI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2023)
Spatial Analysis of the Potential and Status of Soil Damage in Sawan District, Buleleng Regency This study aims to determine the potential and distribution of soil damage status in Sawan District, Buleleng Regency. The research method used is a survey method and a qualitative method of spatial analysis. Based on the results of overlaying land use maps, slope maps, rainfall maps and soil types maps, there are 7 homogeneous land units. The land was taken from homogeneous land units of existing land use, namely natural forests, mixed gardens, settlements and rice fields. After the soil sample was taken, it was continued with soil analysis in the laboratory to determine the bulk density, total porosity, degree of water release, pH, fraction composition, electrical conductivity and number of microbes. The results showed that Sawan District had low soil damage potential at the locations of homogeneous land units I, II, III, and IV and moderate soil damage potential at homogeneous land units V, VI, and VII locations. The status of soil damage in Sawan District is lightly damaged. The parameter causing the damage status in the research area is the water release degree parameter. These parameters get a relative frequency value of 100% with a score of 4 (four). The direction of controlling the status of soil damage that can be done is by providing organic matter and good soil management efforts.